Characteristics of Extreme Hourly Precipitation during Flood Season in Gansu Province from 1990 to 2019 - Li MA; Xiaojun YANG; Yong WANG; Haojun QIN; Yicheng WANG; Junxia ZHANG; Hong'e SHA (Gaoyuan qixiang)
Based on hourly precipitation data of 68 meteorological stations in Gansu Province from 1990 to 2019， the temporal and spatial distribution characteristics and long-term trend of hourly extreme precipitation during main flood season （May-August） in Gansu Province were analyzed by using percentile threshold method from the characteristics of extreme hourly precipitation indices which decided by precipitation， frequency and intensity.It provided effective reference values for further understanding the occurrence regularity of extreme precipitation events in different climatic regions from arid to humid.The results showed that， （1） the extreme hourly precipitation indices decreased from southeast to northwest in Gansu Province.The occurrence of extreme hourly precipitation indices in southwest and southeast of Gansu accounted for a relatively high proportion， and it is the least in Hexi region of Gansu.（2） Extreme hourly precipitation reached its peak in August in southwest and southeast of Gansu， and in July in Hexi and central region of Gansu.The extreme hourly precipitation frequency was the highest in August in Hexi region and southeast of Gansu， and the highest in July in central region and southwest of Gansu.The extreme hourly precipitation intensity was the highest in August in the central region and southwest of Gansu， while the extreme hourly precipitation intensity was the highest in July in Hexi region and southeast Gansu.（3） The climatic trend rates of extreme hourly precipitation， frequency and intensity in Gansu were 6.32 mm·（10a）-1， 0.49 times·（10a）-1 and 0.14 mm·h-1·（10a）-1， respectively， and the increasing trend of precipitation and frequency in Hexi region and southeast of Gansu showed extremely significance.（4） The diurnal variation of extreme hourly precipitation indices in each region showed a single-peak pattern， and the peak value mainly appeared in the afternoon to early midnight.The climatic trend rates of extreme hourly precipitation indices increased in Hexi region and southwest of Gansu in most of the period.From noon to early midnight， the climatic trend rates of extreme hourly precipitation indices weakened in central region and increased in southeast region of Gansu Province.